Philosophical and Anthropological Foundations of Forming High Morality and Spirituality in Young People - Khaidarova Larisa Sunnatovna (Scientific Trends, 2025)
This article explores the philosophical and anthropological foundations of forming high morality and spirituality in young people within the context of contemporary social transformation. The study examines morality and spirituality as fundamental dimensions of human existence and personal development, emphasizing their role in shaping value orientations, ethical behavior, and social responsibility among youth. Drawing on classical and modern philosophical traditions, the article analyzes the interrelation between moral consciousness, spiritual development, and anthropological understanding of the human being. Special attention is given to the impact of globalization, digitalization, and cultural pluralism on the moral and spiritual formation of young people. The research substantiates that the cultivation of high morality and spirituality is a crucial condition for sustainable social development and the formation of a harmonious personality.
Keywords: Morality, spirituality, philosophical anthropology, youth, moral consciousness, values, personal development.